Inflammation and hypertension development: A longitudinal analysis of the African-PREDICT study - Crouch, Simone H. (Int J Cardiol Hypertens, 2020)
BACKGROUND: The role of inflammation in the development of hypertension remains incompletely understood. While single inflammatory mediators have been shown to associate with changes in blood pressure (ΔBP), the role of clusters of inflammatory mediators has been less comprehensively explored. We therefore determined whether individual or clusters of inflammatory mediators from a large biomarker panel were associated with ΔBP over 4.5 years, in young healthy adults. METHODS: We included 358 adults (white, n = 156; black, n = 202) with detailed information on ambulatory blood pressure (BP) at baseline and follow-up. Baseline blood samples were analysed for 22 inflammatory mediators using multiplexing technology. Principal component analysis was used to study associations between clusters of inflammatory mediators and ΔBP. RESULTS: In the total cohort in multivariable-adjusted regression analyses, percentage change in 24hr systolic BP associated positively with Factors 1 (Interferon-gamma, interleukin (IL)-4, IL-7, IL-10, IL-12, IL-17A, IL-21, IL-23, macrophage inflammatory protein (MIP)-1α, MIP-1β, TNF-α, granulocyte-macrophage colony-stimulating factor (GM-CSF)) and 2 (IL-5, IL-6, IL-8, IL-13). Change in daytime systolic BP associated positively with Factors 1, 2 and 3 (C-Reactive protein, IL-1β, IL-2, MIP-3α). Subgroup analysis found these findings were limited to white study participants. Numerous associations were present between individual inflammatory mediators (Interferon-gamma, GM-CSF, IL-4, IL-6, IL-7, IL-8, IL-10, IL-12, IL-13, IL-17A, IL-21, IL-23, MIP-1α and MIP-1β) and ΔBP in the white but not black subgroups. CONCLUSION: We found independent relationships between numerous inflammatory mediators (individual and clusters) and ΔBP over 4.5 years. The relationship between inflammatory markers and ΔBP was only found in white participants. ClinicalTrials.gov (Identifier: NCT03292094)..